Development of carbon-based sensors using recycled ash - Lum, Lucas Yu Xiang (2019)
With the need to reduce the harmful impact of waste on the environment, there is an increased need to recycle the waste produced by the human population. This project explores the possibility of altering the electrical and structural characteristics of waste carbon powder derived from the by-product of oil refining processes through femtosecond laser annealing. The ability to alter the characteristics of the waste carbon assists in determining its feasibility for the future use as an effective gas sensing agent. The electrical and structural characteristics of the carbon powder were measured before and after laser annealing to record the impact made from femto-second laser annealing. The changes to the electrical characteristics were measured through an I-V probe while structural changes were characterised through Raman spectroscopy. Samples of the waste carbon powder were prepared and then subjected to femtosecond laser annealing. The I-V probe results on the carbon samples show a reduced resistance after annealing by as much as a 90% change. An increase in the incident laser power was also found to correspond to an increased reduction in resistance. The experimental and Raman results suggest that femto-second laser annealing has a positive impact on the graphitisation of waste carbon powder. It was also noted that using an average laser power of above 1W has a destructive effect on the carbon powder through an observation of the reduction in carbon powder in the samples subjected to those power levels. While low laser powers of below 0.1W have insufficient power to induce significant graphitisation to the carbon powder shown by the I-V probing and Raman results having a minimal to insignificant change to the electrical and structural characteristics respectively. It was concluded that the range of 0.887 to 1.246W gives the greatest improvement in electrical conductivity to the carbon powder. With the results corresponding to a microstructural change from amorphous carbon to nano-crystalline carbon as explained by the Raman data against the 3-stage model. Therefore, there is a potential for femto-second laser annealing as a method to alter structural and electrical characteristics of waste carbon powder. Opening the possibility for the functionalisation of waste carbon for use in future electronics and sensors applications.